Bond with God as a Moderator of the Relationship between Prayer and Stress of Chilean Students - Wnuk, Marcin (Religions, 2023)
Prayer is a spiritual coping method that can be effective both in extraordinary, life-threatening circumstances and in ordinary, stressful situations. To be beneficial, it requires a bond with God or the divine based on trust and faith. The purpose of this study was to examine the mediated moderation model in which spiritual experiences moderate the link between prayer and stress, which in turn, is negatively related to the subjective well-being of Chilean students. The study’s participants were 177 students from Chile. The following tools were used: Daily Spiritual Experiences Scale, two measures regarding the quality of life and negative feelings from the World Health Organization Quality of Life—BREF, one tool verifying stress from the National Health Interview Survey and one-item scale in reference to frequency of praying. This study confirmed the mechanism underpinning the relationship between prayer and subjective well-being, as well as the benefits of a bond with God and the harmful role of stress in this relationship. When students more frequently felt God’s love and direction, prayer was negatively related to stress, which in turn, negatively predicted subjective well-being. For students with a poor bond with God and fewer spiritual experiences, prayer was positively linked with stress. This study confirms the benefits of a close, trusting bond with God or the divine and the detrimental effects of lacking a positive connection with God on students’ stress when students used prayer as a coping method. The practical implications of this study are also presented.